Hubungan Pola Asuh Terhadap Perilaku Prososial Pada Remaja SMPN X Di Kota Bekasi - Nadya Lestari; Netty Merdiaty (Jurnal Kajian Ilmiah, 2023)
This study describes the relationship between parenting style and prosocial behavior in class VII to IX students in Bekasi City. This study aims to determine whether there is a relationship between parenting atyle and prosocial behavior using 115 respondents who are students of SMPN X Kota Bekasi. The method used in this study was Spearman’s correlation analysis to dee the relationship between the two variables studies and the data analysis process using the help of IBM SPSS 25 software. The results in this study showed a significance value of 0.000 or p < 0.05, so it was expressed by the value of the correlation coefficient equal to 0.508**, which indicates a relationship between the two variables with a positive relationship with the direction of the moderate category. Based on the correlation test results, it was fount that H0 was rejected and Ha was accepted; namely, there was a relationship between parenting style and prosocial behavior. So to improve students prosocial behavior, the advice that can be given to parents is to review the parenting style that will be given to children so that they can routinely hold meetings related to student behavior at school and for students to actively participate in activities maintained by the school to improve prosocial behavior.